Znaczenie outplacementu w procesie derekrutacji - Mróz, Joanna (The Role of Outplacement in Process of Employment Reduction, 2008)
The problem of outplacement has been presented in the paper. After the presentation of the essence and effects of the employment reduction, the term outplacement has been defined. Than typologies of outplacement has been described. Later on the advantages of outplacement for employees and firms have been pointed out. Finally the measures of effectiveness of outplacement have been focused on. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 168-175